Needs and challenges of lay community health workers in a palliative care environment for orphans and vulnerable children - Bonita Bernice Visagie; Jace Pillay (AOSIS, 2017)
Introduction: The escalation of HIV/AIDS infections in the last decade has increased the need for palliative care community organizations to care for orphans and vulnerable children, who are in dire need of support. Many of these organizations depend on the services of lay community health workers to provide constant care to those in need of it in their local communities. The focus of this study is to explore the role of lay health workers in a community organization located in rural Bronkhorstspruit, Gauteng Province of South Africa. That provides palliative care for orphans and vulnerable children diagnosed with HIV/AIDS. Their roles were analysed critically through a job-demands and job-resources theoretical framework. Methods: A descriptive phenomenological case study design was employed to collect data through twenty five individual interviews, two separate focus groups consisting of ten participants in one group and eleven participants in the other group, observations and document analysis. Data were processed through a rigorous thematic analysis. Results: The findings pointed out specific knowledge and skills these lay community health workers needed in order to be satisfied with, and successful in, their administration of palliative care to orphans and vulnerable children. Participants identified the following organizational challenges that were deemed to be impacting negatively on their work experiences: the lack of career pathing processes; sufficient career guidance; and inadequate employment processes, such as staff retention, succession planning, and promotion. Conclusion: Through the findings, a framework for enhancing the work experiences of the lay community health workers was developed. The uniqueness of this framework is that the focus is on improving the work lives of the lay community health workers, who have serious skills-resourcing needs. There were specific concrete strategies that the organization could adopt to support the knowledge and skills requirements of the lay community health workers in relation to the needs and challenges that will enhance their efficiency in the palliative care environment. The findings and framework that emanated from this study could be used to support lay community health workers in their respective organizations to be more effective in the support they provide to orphans and vulnerable children. Because South Africa is afflicted by the HIV/AIDS epidemic, this framework can be used in similar organizations that are working with lay community health workers with skill-resourcing needs not only in the health sector, but also in other sectors, such as in education and agriculture.